Feasibility Study of Emission Reduction on Marine Engine with Variation of Emulsified Water Concentration and Turbocharger Compression Ratio - Iksoo Choi (Applied Sciences, 2020)
The characteristics of black carbon and nitrogen oxide reduction versus the water content of emulsion fuel were studied by numerical methods, and a method of reducing fuel consumption was achieved by adjusting the turbocharger compression ratio. The results of the combustion period characteristics, versus the three types of emulsion fuel and the turbocharger compression ratios, shows that the combustion period is shortened in the order of CR00 > CR01 > CR02 > CR03, according to the compression ratio of the turbocharger. As the fuel water content increases, the combustion period is shortened in the order of EMDO16 < EMDO13 < EMDO10. The nitrogen oxide and black carbon reduction was because the combustion period increased, with increasing compression ratio, while the combustion period was shortened, with increasing moisture content of emulsion fuel. This also caused is an increase in the combustion pressure and a shortening of the combustion period, due to the expansion of the volume, in turn due to the micro-explosion of water. This may be due to the shortening of the post combustion period and the reduction of black carbon emissions. In addition, combustion was accelerated in the order—CR00 > CR01> CR02> CR03. By optimizing the water content of the emulsion fuel and turbocharger compression ratio, while considering the exhaust emission and combustion state, reduction of the fuel consumption rate and output improvement are shown.